Right iliac fossa lump: a diagnostic surprise - Chandhirasekar, Balaji; Neogi, Sushanto (International Surgery Journal, 2019)
A 42 years gentleman presented with recurrent urinary tract infection and intermittent lump in the right side of abdomen for 4 months. Clinically, soft cystic lump in the right iliac fossa with ill-defined lower margins, and disappeared on micturition. Contrast enhanced CT urography showing a large urinary bladder diverticulum of 107mm×52 mm. Cystoscopy confirmed a bladder diverticulum on left lateral wall of urinary baldder, superolateral to left ureteral orifice with no bladder trabeculations and bilateral normal ureteric orifice. Patient underwent open diverticulectomy with primary repair of urinary bladder wall done. Histopathology confirmed the presence of all layers in the wall of diverticulum. Postoperative period was uneventful. Patient resolved of symptoms in the 6 month follow up period.